Warming of +1.5 °C is too high for polar ice sheets - Chris R. Stokes; Jonathan L. Bamber; Andrea Dutton; Robert M. DeConto (Communications Earth & Environment)
Abstract Mass loss from ice sheets in Greenland and Antarctica has quadrupled since the 1990s and now represents the dominant source of global mean sea-level rise from the cryosphere. This has raised concerns about their future stability and focussed attention on the global mean temperature thresholds that might trigger more rapid retreat or even collapse, with renewed calls to meet the more ambitious target of the Paris Climate Agreement and limit warming to +1.5 °C above pre-industrial. Here we synthesise multiple lines of evidence to show that +1.5 °C is too high and that even current climate forcing (+1.2 °C), if sustained, is likely to generate several metres of sea-level rise over the coming centuries, causing extensive loss and damage to coastal populations and challenging the implementation of adaptation measures. To avoid this requires a global mean temperature that is cooler than present and which we hypothesise to be closer to +1 °C above pre-industrial, possibly even lower, but further work is urgently required to more precisely determine a ‘safe limit’ for ice sheets.